Feeling Authentic on Social Media: Subjective Authenticity Across Instagram Stories and Posts. (March 2022) - Kreling, Rebekka; Meier, Adrian; Reinecke, Leonard
Self-presentation on social network sites (SNS) such as Instagram is often assumed to be inauthentic or even fake. While authenticity on SNS has been linked to increased well-being, most research has investigated it either monolithically (e.g., via screen time measures) or with regard to stable self-presentations (e.g., in Facebook profiles). In contrast, this study compares subjective authenticity perceptions within users and between self-presentations via two SNS features—Stories vs Posts. Drawing on the affordances approach, we theorize and test whether and how Stories produce greater state authenticity than Posts. Results from a preregistered within-subjects study comparing self-reports on N = 489 Posts and N = 546 Stories from N = 202 Instagram users show that by allowing more spontaneous self-presentation, Stories indeed produced (slightly) higher authenticity perceptions than Posts. However, subjective authenticity was high in both features, indicating that they similarly offer a space for authentic online self-presentation.